1983
DOI: 10.1016/s0006-3495(83)84356-2
|View full text |Cite
|
Sign up to set email alerts
|

Quenching-resolved emission anisotropy studies with single and multitryptophan-containing proteins

Abstract: Measurements of the anisotropy of protein fluorescence as a function of an added collisional quencher, such as acrylamide, are used to construct Perrin plots. For single tryptophan containing proteins, such plots yield an apparent rotational correlation time for the depolarization process, which, in most cases, is approximately the value expected for Brownian rotation of the entire protein. Apparent limiting fluorescence anisotropy values, which range from 0.20 to 0.32 for the proteins studied, are also obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
36
1

Year Published

1986
1986
2012
2012

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(48 citation statements)
references
References 51 publications
11
36
1
Order By: Relevance
“…The limiting anisotropy for a completely immobilized Trp is 0.31 (28). Because of the size of F 1 , the depolarization caused by rotational diffusion of the protein (estimated rotational correlation time Ϸ200 ns) during the fluorescence lifetime of Trp (Ͻ10 ns; see ref.…”
Section: Subunitmentioning
confidence: 99%
“…The limiting anisotropy for a completely immobilized Trp is 0.31 (28). Because of the size of F 1 , the depolarization caused by rotational diffusion of the protein (estimated rotational correlation time Ϸ200 ns) during the fluorescence lifetime of Trp (Ͻ10 ns; see ref.…”
Section: Subunitmentioning
confidence: 99%
“…Fluorescence anisotropy was analyzed by the Perrin equation (3) where A is the anisotropy, A 0 is the limiting anisotropy in the absence of molecular motion, τ is the lifetime, and θ is the rotational correlation time (34). The limiting anisotropy A 0 is obtained by plotting 1/A versus F/F 0 since the relative change in the lifetime is as follows τ ≡ τ rel = τ/τ 0 = F/F 0 .…”
Section: Fluorescence and Absorption Spectroscopymentioning
confidence: 99%
“…Proteins are complex systems often exhibiting both soft regions and rigid and compact domains [9,10]. Using the fluorescence approach, many authors have reported movements of Tyr and Trp residues in various proteins [11–14]. Other studies were carried out on a time‐dependent dipolar re‐orientation of the environment surrounding the Trp residue [15].…”
mentioning
confidence: 99%